Social Behavior of Pet Dogs Is Associated with Peripheral OXTR Methylation - Cimarelli, Giulia; Virányi, Zsófia; Turcsán, Borbála; Rónai, Zsolt; Sasvári-Székely, Mária; Bánlaki, Zsófia (Frontiers in Psychology, 2017)
Oxytocin is a key modulator of emotional processing and social cognitive function. In line with this, polymorphisms of genes involved in oxytocin signaling, like the oxytocin receptor (OXTR) gene, are known to influence social behavior in various species. However, to date, no study has investigated environmental factors possibly influencing the epigenetic variation of the OXTR gene and its behavioral effects in dogs. Pet dogs form individualized and strong relationships with their owners who are central figures in the social environment of their dogs and therefore might influence the methylation levels of their OXTR gene. Here we set out to investigate whether DNA methylation within the OXTR promoter region of pet dogs is linked to their owner's interaction style and to the social behavior of the dogs. To be able to do so, we collected buccal epithelial cells and, in Study 1, we used pyrosequencing techniques to look for differentially methylated CpG sites in the canine OXTR promoter region on a heterogeneous sample of dogs and wolves of different ages and keeping conditions. Four identified sites (at positions −727, −751, −1371 and −1383 from transcription start site) showing more than 10% methylation variation were then, in Study 2, measured in triplicate in 217 pet Border Collies previously tested for reactions to an adverse social situation (i.e., approach by a threatening human) and with available data on their owners’ interaction styles. We found that CpG methylation was significantly associated with the behavior of the dogs, in particular with the likelihood that dogs would hide behind their owner or remain passive when approached by a threatening human. On the other hand, CpG methylation was not related to the owners' behavior but to dog sex (at position −1371). Our findings underpin the complex relationship between epigenetics and behavior and highlight the importance of including epigenetic methods in the analysis of dog behavioral development. Further research is needed to investigate which environmental factors influence the epigenetic variation of the OXTR gene.